Campylobacter species in animal, food, and environmental sources, and relevant testing programs in Canada - Huang, Hongsheng; Brooks, Brian W; Lowman, Ruff; Carrillo, Catherine D (Canadian journal of microbiology, 2015)
Campylobacter species, particularly thermophilic campylobacters, have emerged as a leading cause of human foodborne gastroenteritis worldwide, with Campylobacter jejuni, Campylobacter coli, and Campylobacter lari responsible for the majority of human infections. Although most cases of campylobacteriosis are self-limiting, campylobacteriosis represents a significant public health burden. Human illness caused by infection with campylobacters has been reported across Canada since the early 1970s. Many studies have shown that dietary sources, including food, particularly raw poultry and other meat products, raw milk, and contaminated water, have contributed to outbreaks of campylobacteriosis in Canada. Campylobacter spp. have also been detected in a wide range of animal and environmental sources, including water, in Canada. The purpose of this article is to review (i) the prevalence of Campylobacter spp. in animals, food, and the environment, and (ii) the relevant testing programs in Canada with a focus on the potential links between campylobacters and human health in Canada.